The Morality of Flexing: An Analysis of Unethical Recruitment Strategies in Digital Gig Economy from Religious Perspective - Elisabet Halida Wahyarsi; Arissetyanto Nugroho; Seta A Wicaksana (International Journal of Social Science and Religion (IJSSR), 2026)
The rapid growth of the digital gig economy has given rise to a new and controversial profession: Binary Option platform affiliates, who frequently employ the "flexing" marketing strategy (excessive displays of wealth) to attract customers. This phenomenon has become a serious problem in Human Resource Management (HRM) due to the use of psychological manipulation and dishonest information in the recruitment process for new users or partners. This activity often traps customers in a speculative and illegal system, substantially resembling online gambling. This study aims to analyze the morality of flexing-based recruitment strategies through the lens of HRM ethics and interfaith perspectives, particularly Islam and Christianity, to examine the social and spiritual impacts of this digital economic malpractice. This study uses qualitative methods with a descriptive and comparative approach between positive law and religious norms in Indonesia and Singapore. The analysis examines affiliate marketing practices and religious texts relevant to the ethics of earning a living and honesty. Flexing is an unethical recruitment strategy because it violates the principles of transparency and professional integrity, where commissions are derived from the losses of others (loss-sharing). This practice is identified as a form of Riya (showing off) and support for Maysir (gambling) and Gharar (uncertainty/fraud), which are strictly prohibited in Islamic economic law because they harm others for personal gain. From a Christian perspective, this strategy contradicts the principle of honesty towards others and the warning about the "Love of Money" as the root of evil, and ignores the value of humility and moral responsibility in managing God's blessings. The difference in policy in Indonesia, which prohibits Binary Options as gambling, compared to Singapore, which strictly regulates it, shows how religious morality values ​​influence public policy. The study concludes that flexing in the digital gig economy is not just a social trend, but a crisis of recruitment morality. The integration of Islamic and Christian values ​​can provide a strong ethical foundation to strengthen digital HR regulations and protect society from fraud-based economic exploitation.